Annual Plan 2006-07 Volume - II (Sectoral Programmes) A. Economic Services Government of Andhra Pradesh - Planning Commission (Planning Commission, 2006)
Andhra Pradesh is the 5th largest State among the Indian States population wise. Its population as per 2001 census is 76.2 million. State contributes to 7.41% of India's total population (1027 million). Estimated population of the State as on 1st March, 2006 is 81.6 million. Geographically it is the 4th largest State in the country with an area of 275.00 sq. K.Ms. Around 23.7% (Advance estimates:2005-06) of the state GDP is from Agriculture and Allied Services, providing employment to around 65% of the state's population. The state enjoys a position of pre-eminence in respect of crop production.
Planning Department, Government of Andhra Pradesh